Comparison of Completed Cohort Fertility Rate and Total Fertility Rate in selected European countries - Kharashvili, Sopio; Miskolczi, Martina; Hon, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
Nowadays, the world is struggling with challenges related to population dynamics, where fertility plays a critical role in shaping these processes. One of the most crucial concerns is the risk of the world’s population decreasing due to low fertility rates. This issue is particularly notable in many developed regions, including the European Union, where fertility rates have been declining steadily over the past few decades. As fertility rates drop below the replacement level of 2.1 children per woman, countries face significant demographic challenges that could impact economic stability, social structures, and the overall sustainability of their populations. Demographic transitions, which refer to the shift from high birth and death rates to low birth and death rates, are integral to understanding these changes. Typically, this transition involves an initial population surge followed by a stabilization or decline. In the context of many developed countries, this transition has reached a stage where low fertility rates are prevalent, leading to aging populations and shrinking workforces. These demographic shifts are significant as they influence economic growth, social services, and policy decisions. Addressing the implications of demographic transitions requires a thorough understanding of fertility indicators such as Total Fertility Rate (TFR) and Cohort Completed Fertility Rate (CCFR). Both indicators are essential for policymakers to assess and project fertility trends, understand reproductive behaviour, and anticipate future population changes. Several factors contribute to declining fertility rates, each varying in impact across different populations and cultural contexts, such as economic conditions, cultural norms, gender equality, improved reproductive health services, and the availability of contraceptive options, each of which empowers individuals to make informed decisions about their reproductive lives.
In response to these challenges, various countries within the European Union have implemented a range of measures aimed at encouraging higher birth rates such as financial incentives like child allowances, tax benefits, and parental leave payments which provide direct support to families. Understanding the different aspects of fertility rates and the effectiveness of various policy measures is crucial to addressing the challenges posed by declining birth rates. This research aims to explore these aspects by providing a comprehensive analysis of the current state of fertility rates, the factors influencing these trends, and the strategies used to prevent the trend of population decrease. By examining these elements, we can better understand how to support sustainable population growth and ensure the long-term viability of our societies. Such an understanding is vital for developing effective policies that promote a balanced and thriving population, capable of sustaining economic and social well-being.
Vedoucí práce: Martina Miskolczi
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses